Маркетинговий аналіз ринку банківських послуг в Україні : цілі, завдання та проблеми - Гавриш, Ірина Іванівна; Бабух, Ілона Борисівна; Ібрагімов, Еміль Юсирович (Ефективна економіка. Вип. 8. 2022., 2022)
УстаттівизначаютьсяключовіхарактеристикитаосновнізавданняіпроблемимаркетинговогоаналізуринкубанківськихпослугвУкраїні. Впливбанківськоїсистеминаекономікузалежитьвідякостірозвиткусамоїбанківськоїсистеми, відзастосуваннянеюновітніхфінансовихтехнологійнабазідіджиталізації. Новітнітенденціїнаринкубанківськихпослугякразіпідкреслюютьтойфакт, щовуправліннібанкомівтеоретичній, івпрактичнійплощинімаєдомінуватимаркетинговийпідхід. Маркетинговийаналізринкубанківськихпослугсвоюспецифікувизначаєспецифічнимиособливостямибанківськихпродуктівіпослугтатоюроллю, якувінвідіграєяквкомплексімаркетингубанку, таківціломувсистемійогоуправліннязадлязабезпеченняприбутковості, ліквідностітареалізаціїсоціальноїфункціївсуспільстві. Маркетинговийаналізвбанкуспрямованийнапошукможливостейбанкузайнятиконкурентніпозиціїнаконкретномуринкуабойогосегментічерезпристосуваннясвоїхпродуктівдопопитуівимогклієнтів, прицьомусегментуваннядаєможливістьчітковизначитицільовийриноктайогопотреби, окреслюватиперевагиінедолікибанкувконкурентнійборотьбі, створюєнеобхіднубазудлярозробкидовгостроковоїстратегіїбанку. Типовазагальнасхемамаркетинговогоаналізувбанкувирішуєколостандартнихзавдань, забезпечуючиреалізаціюосновноїметимаркетинговогоаналізуринкубанківськихпослуг – виявлятизмінинаньому, прогнозуватиїхтаоперативнонанихреагувати. Томусхемумаркетинговогоаналізувикористовуютьіприаналізіосновнихгрупбанківськихпослуг, класифікаціюякихнайчастішепроводятьзаїхекономічноюприродоютапризначенням. Системниймаркетинговийаналізнаціленийнавиявленняпріоритетноїпроблеми, якастоїтьпередбанкоміправильнеформулюваннятихзавдань, рішенняякихдопоможебанкувирішитицюпроблему. Врамкахмаркетинговогоаналізувиокремлюютьокремівидимаркетинговихдосліджень, атакожнайважливішіскладовіелементи. Важливим інструментоммаркетинговогоаналізувиступаєпрогнозування, впершучергупрогнозвпливунапопитнабанківськіпослугивнутрішніхізовнішніхчинників. Діджиталізація, постковідніреаліїтаросійсько-українськавійназначнозмінилиумовинаринкубанківськихпослуг, ускладнилиїхтаводночасвпотенціїбудутьсприятикардинальнимзмінамвбанківництві. The article defines the main characteristics, tasks and problems of marketing analysis of the market of banking services in Ukraine. The influence of the banking system on the economy depends on the quality of development of the banking system itself, on its application of the latest financial technologies based on digitization. The latest trends in the market of banking services underline the fact that the marketing approach should dominate bank management both theoretically and practically. Marketing analysis of the market of banking services determines its specificity by the specific features of banking products and services and by the role it plays in the bank's marketing complex and in its management system as a whole in order to ensure profitability, liquidity and the realization of a social function in society. Marketing analysis in the bank is aimed at finding opportunities for the bank to take a competitive position in a specific market or its segment by adapting its products to customer demand and requirements, while segmentation makes it possible to define the target market and its needs, outline the bank's advantages and disadvantages in competition, creates the necessary basis for developing the bank's long-term strategy. A typical general scheme of marketing analysis in a bank solves a range of standard tasks, ensuring the realization of the main goal of marketing analysis of the banking services market - to detect changes in it, forecast them and promptly respond to them. Therefore, the scheme of marketing analysis is also used in the analysis of the main groups of banking services, the classification of which is most often carried out according to their economic nature and purpose. System marketing analysis is aimed at identifying the priority problem facing the bank and correctly formulating those tasks, the solution of which will help the bank to solve the problem. As part of the marketing analysis, separate types of marketing research are distinguished, as well as the most important constituent elements. Forecasting is an important tool of marketing analysis, primarily forecasting the impact of internal and external factors on the demand for banking services. Digitization, post-Covid realities and the Russian-Ukrainian war significantly changed the conditions in the banking services market, made them more difficult, and at the same time would potentially contribute to radical changes in banking.
Маркетинговий аналіз ринку банківських послуг в Україні : цілі, завдання та проблеми
Keywords: Ключовіслова: маркетинговийаналіз, маркетингбанківськихпослуг, ринокбанківськихпослуг, комплексмаркетингу, банк, діджиталізація, індивідуалізаціяпослуг. Keywords:marketing analysis, marketing of banking services, market of banking services, marketing complex, bank, digitalization, individualization of services.